OBTENÇÃO DE CATALISADORES HETEROGÊNEOS PARA REAÇÃO DE TRANSESTERIFICAÇÃO - Tavares, Mauro Henrique Almeida (2010)
The biodiesel is produced mainly via homogeneous catalysis, however this process presents some disadvantages such as saponification of esters and the difficulty of separating the catalyst of the formed products. In this work ceramic catalysts were prepared from the application of the surface coating, nanometrics, BaO, CaO and MgO in commercial alumina, in order to improve the catalytic activity in the transesterification reaction, mainly triglycerides. The catalysts were obtained from the surface modification of alumina using a combined technique between sol-gel and polymeric precursors. The obtained catalysts were characterized by Infrared Spectroscopy techniques with Fourier Transform, Scanning Electron Microscopy, Electronic, Optical Microscopy, X-rays Diffraction and Analysis of gas adsorption. The coating in nanometric was observed in only a few particles of support. It was observed that the characteristics of support are essential to obtaining the catalysts for the reaction transesterification of babassu oil, as regards the conversion and processing. The catalysts of alumina with BaO, CaO and MgO showed catalytic for the production of biodiesel. However, with 5 % catalyst in reaction to oil, all catalysts have income above 90 %. Thus, the catalysts were effective for the transesterification of babassu oil for the production of biodiesel.